Autophagy plays an essential role in ultraviolet radiation-driven skin photoaging - Ma, Jingwen; Teng, Yan; Huang, Youming; Tao, Xiaohua; Fan, Yibin (Frontiers in Pharmacology, 2022)
Photoaging is characterized by a chronic inflammatory response to UV light. One of the most prominent features of cutaneous photoaging is wrinkling, which is due primarily to a loss of collagen fibers and deposits of abnormal degenerative elastotic material within the dermis (actinic elastosis). These changes are thought to be mediated by inflammation, with subsequent upregulation of extracellular matrix-degrading proteases and down-regulation of collagen synthesis. Autophagy is a vital homeostatic cellular process of either clearing surplus or damaged cell components notably lipids and proteins or recycling the content of the cells’ cytoplasm to promote cell survival and adaptive responses during starvation and other oxidative and/or genotoxic stress conditions. Autophagy may also become a means of supplying nutrients to maintain a high cellular proliferation rate when needed. It has been suggested that loss of autophagy leads to both photodamage and the initiation of photoaging in UV exposed skin. Moreover, UV radiation of sunlight is capable of regulating a number of autophagy-linked genes. This review will focus on the protective effect of autophagy in the skin cells damaged by UV radiation. We hope to draw attention to the significance of autophagy regulation in the prevention and treatment of skin photoaging.